Revitalizing the household of God as model church - Cacho, Rebecca G. (Animo Repository, 2022)
This paper retrieves the ecclesiological model of the household of God and appropriates it within our present context in order to appreciate the meaning and relevance of being Church in our time. The church in the home exemplifies ecclesiastical ministries originating from the mission of proclaiming the kingdom of God, namely, koinonia, kerygma,leitourgia, diakonia, and marturia. As a household of God, the Church embodies being gathered as a community by the Spirit of Jesus. To be a “church is more than simply a meeting; more than a loose and casual gathering as when people get together for a party” because it is a community where people share their life together in the fellowship of love and true family spirit (cf. Acts of the Apostles 4-5). This involves a mutual commitment of each member to all the other members. All Christians are children of God and brothers and sisters to each other. This kind of commitment requires that those who are gathered together enter into a covenant with one another to ensure the well-being of every family member. Just like human families, the Church, as a household of God, dedicates all its efforts to realizing God’s kingdom. Their love and communion testify to God’s motherly/fatherly love for the children born out of God’s unparalleled benevolence to humanity (cf. Isa. 49: 15-16).